Literature and the Munich Crisis. Issue 2 (November 2013) - Ellis, Steve
The upheaval, moral self-questioning and uncertainty into which the Munich negotiations and settlement of September 1938 threw the British nation are examined in a series of now almost totally forgotten works which constitute the genre of the 'Munich Crisis novel'. These are then related to better known post-Munich writings by, among others, Forster, Woolf, Orwell, MacNeice and Patrick Hamilton. A range of reactions to the crisis – pro- and anti-appeasement, pacifism, anxiety over air bombardment, paralysis, dilemma – thus emerge as components of what Forster analysed as 'the 1939 State', and which this article substantiates in greater detail.